The Influence of Guest Stars, Prices, And Event Marketing on The Decision of Tourists Visiting the Allobank Festival - Gustian Alkahfi; Liliana Dewi; Ulfi Maranisya (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The AlloBank Festival is a music event for the introduction of Bank Allo, which will be held at Istora Senayan 20-22 May 2022, which will bring in various interesting guest stars such as the main guest stars from South Korea NCT and RedVelvet as well as several major Indonesian stars such as Ari Lasso, BCL, Tulus, Pamungkas, Ran, Hivi and many others. This research is a quantitative study to measure the effect of Guest Star independent variable (X1), Price independent variable (X2), and Event Marketing independent variable (X3) on the dependent variable of Tourist Visiting Decision (Y) to AlloBank Festival with multiple linear regression analysis methods through distributing questionnaires using random sampling of 100 respondents. This study showed that the independent variables of guest star, price, and event marketing had a significant influence on the Decision of tourists to visit the AlloBank Festival.